Milk composition and yield of the Red Sokoto (Maradi) goats in Nigeria - Akinsoyinu, A.O.; Tewe, O.O.; Ngere, L.O.; Mba, A.U. (1981)
Studies the milk and colostrum composition, milk yield and total solids of Red Sokoto (Maradi) goats in Nigeria over three consecutive lactation periods.